Synthesis and in vitro anti Mycobacterium tuberculosis activity of a series of phthalimide derivatives - Santos, Jean L. [UNESP]; Yamasaki, Paulo R. [UNESP]; Chin, Chung Man [UNESP]; Takashi, Celio H. [UNESP]; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
New phthalimide derivatives were easily prepared through condensation of phthalic anhydride and selected amines with variable yields (70-90%). All compounds (3a-l) were evaluated against Mycobacterium tuberculosis H(37)Rv using Alamar Blue susceptibility. The compounds 3c, 3i, and 3l have the minimum inhibitory concentrations (MICs) of 3.9, 7.8, and 5.0 mu/mL, respectively, and could be considered new lead compounds in the treatment of tuberculosis and multi-drug resistant tuberculosis. Crown Copyright (C) 2009 Published by Elsevier Ltd. All rights reserved.
Keywords: Phthalimide derivatives; Antimycobacterial; Antitubercular activity; Cytotoxicity